Impact of Economic Crisis on Passenger Transportation – Case of Travelling to the Greek Mainland from Crete - Eleni Chita; Efi Drimili; Zoe Gareiou; Christina Milioti; Antigoni Vranna; Stavros Poulopoulos; Efthimios Zervas (Promet - Traffic&Transportation, 2020)
The Greek economic crisis of 2009 onwards has affected all aspects of social and economic life of the country, including transportation. The present study focuses on the impact of economic crisis on the long distance transportation between the island of Crete in Greece, the largest Greek island and one of the largest in the Mediterranean Sea, and the Greek mainland. A questionnaire survey was used to investigate the opinions of the Cretans on the way the economic crisis influenced their transportation to the Greek mainland. The results of the survey show that the frequency of the Cretans’ travels was significantly limited, owing to the increased direct or indirect associated cost, due to the economic crisis. Especially for those who struggled to make ends meet, the transportation to the mainland dropped to the bare essentials. Furthermore, the respondents deemed that the deregulation of the Greek maritime and airline markets was also to blame for the high fares, thus they favoured a regulated public transport sector and were against privatization. Inevitably, financially vulnerable individuals were the most preoccupied with these issues. A feeling of isolation and exclusion was revealed by the sample on occasions when the scheduled trips were cancelled by the operators due to exogenous parameters.